Kampung Wisata Purbayan: Harmonization of religious values and socio-cultural identity in community based tourism development - Windi Novia Ratri Wardhani; Ratih Pratiwi; Muhammad Thohir; Luluk Mubarokah; Julio Valen DB; Ari Setiawan (Universitas Sarjanawiyata Tamansiswa, 2023)
This study examines the potential for halal tourism by investigating the relationship between religion and socio-cultural identity in Kamwis Purbayan, DIY. This study refers to a literature survey and direct observation approach which is strengthened by data and information from reliable sources. The findings show that religious teachings, along with local culture, are one of the positive elements that influence the adoption of cultural and religious heritage tourism in Kamwis Purbayan. Kamwis Purbayan is the forerunner to the emergence of Islamic Mataram in Java. The existing Islamic principles are represented in the form of physical culture, in addition to those embraced by the community and used as a reference in daily activities. Furthermore, the interaction between religious values and traditional values is well presented both in buildings, regional structuring, social life systems and also cultural systems that are still growing strong today. This supports the symbiotic relationship shown in the form of constructive support between religion, culture, social engagement and the tourism business at Kamwis Purbayan in the context of halal tourism.